2017
DOI: 10.1371/journal.pone.0181976
|View full text |Cite
|
Sign up to set email alerts
|

ACE phenotyping in human heart

Abstract: AimsAngiotensin-converting enzyme (ACE), which metabolizes many peptides and plays a key role in blood pressure regulation and vascular remodeling, is expressed as a type-1 membrane glycoprotein on the surface of different cells, including endothelial cells of the heart. We hypothesized that the local conformation and, therefore, the properties of heart ACE could differ from lung ACE due to different microenvironment in these organs.Methods and resultsWe performed ACE phenotyping (ACE levels, conformation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…As ACE glycosylation could be both cell- and tissue-specific due to different post-translational modification of ACE globule in different cells, the local topography of ACE surface produced by different cells could be also unique. We demonstrated previously that the pattern of ACE binding by a set of mAbs to 16 epitopes of human ACE–"conformational fingerprint of ACE"–is indeed cell- and tissue-specific [5, 910] and, moreover, confirmed that tissue-specific glycosylation of ACE is an important structural requirement for this specific “conformational fingerprint” [1012].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…As ACE glycosylation could be both cell- and tissue-specific due to different post-translational modification of ACE globule in different cells, the local topography of ACE surface produced by different cells could be also unique. We demonstrated previously that the pattern of ACE binding by a set of mAbs to 16 epitopes of human ACE–"conformational fingerprint of ACE"–is indeed cell- and tissue-specific [5, 910] and, moreover, confirmed that tissue-specific glycosylation of ACE is an important structural requirement for this specific “conformational fingerprint” [1012].…”
Section: Introductionmentioning
confidence: 63%
“…In order to save valuable mAbs, we used not more than 3 μg/ml of pure mAbs (or 1/20 dilution of hybridoma cell culture medium) which was found to be sufficient for coating (Fig 1C and 1D). Usually the amount of ACE immunoreactive protein was estimated using the strongest mAb to ACE, clone 9B9 [16, 20], while a pattern of ACE activity precipitation by a panel of mAbs to different epitopes on ACE—conformational fingerprint of ACE—was used for the estimation of local conformational differences in ACE surface topography due to disease [5, 7, 21] or due to tissue origin of ACE [5, 9, 10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations